2013
DOI: 10.1152/ajpendo.00441.2013
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity and metabolic flexibility following exercise training among different obese insulin-resistant phenotypes

Abstract: Malin SK, Haus JM, Solomon TP, Blaszczak A, Kashyap SR, Kirwan JP. Insulin sensitivity and metabolic flexibility following exercise training among different obese insulin-resistant phenotypes. Am J Physiol Endocrinol Metab 305: E1292-E1298, 2013. First published September 24, 2013; doi:10.1152/ajpendo.00441.2013.-Impaired fasting glucose (IFG) blunts the reversal of impaired glucose tolerance (IGT) after exercise training. Metabolic inflexibility has been implicated in the etiology of insulin resistance; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 42 publications
8
70
3
Order By: Relevance
“…For example, given that impaired postabsorptive fat oxidation predicts the severity of insulin resistance (37) and subjects with low rates of postabsorptive fat oxidation improve to a greater extent because of training (26), it is possible that the "window for adaptation" was not sufficiently large for our subjects to benefit from training. Indeed, postabsorptive NPRER for the HIIT group prior to the training intervention in our study (ϳ0.79) was lower than that which was present pretraining for the subjects of Goodpaster et al (26) and that which has been reported for obese metabolically inflexible individuals (37,43). Consequently, it appears as if metabolic flexibility in our at-risk subjects was quite high prior to training (e.g., ⌬NPRER Ϸ 0.14), which means that the present findings cannot be used as conclusive proof that HIIT without bodyweight loss does not improve metabolic flexibility in metabolically inflexible subjects.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…For example, given that impaired postabsorptive fat oxidation predicts the severity of insulin resistance (37) and subjects with low rates of postabsorptive fat oxidation improve to a greater extent because of training (26), it is possible that the "window for adaptation" was not sufficiently large for our subjects to benefit from training. Indeed, postabsorptive NPRER for the HIIT group prior to the training intervention in our study (ϳ0.79) was lower than that which was present pretraining for the subjects of Goodpaster et al (26) and that which has been reported for obese metabolically inflexible individuals (37,43). Consequently, it appears as if metabolic flexibility in our at-risk subjects was quite high prior to training (e.g., ⌬NPRER Ϸ 0.14), which means that the present findings cannot be used as conclusive proof that HIIT without bodyweight loss does not improve metabolic flexibility in metabolically inflexible subjects.…”
Section: Discussioncontrasting
confidence: 59%
“…Similarly, endurance training improves fasting fat oxidation in older obese subjects with impaired glucose tolerance (57) and nonobese subjects with Type 2 diabetes (61). However, the ability of endurance training to increase fasting fat utilization might depend upon the intensity/volume of exercise, the severity of pathological progression, and/or whether caloric restriction and weight loss accompany training (26,43).…”
mentioning
confidence: 99%
“…Twenty older obese adults (Table 1) volunteered for this study, and a subgroup had participated in a previous investigation (13). They were nonsmokers, weight stable (<2-kg weight loss during the previous 6 months), and sedentary (exercising <60 min·wk −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…or took medications known to affect glucose metabolism. Before metabolic testing, subjects were fed isocaloric meals (resting metabolic rate × 1.2 activity factor; 55% CHO, 30% fat, 15% protein) and instructed to refrain from vigorous physical activity for 3 d. Subjects underwent 12 wk of supervised exercise, which consisted mainly of aerobic treadmill walking performed at 85% HR max for 60 min·d −1 , as previously described (13). Postintervention metabolic testing was conducted approximately 16–18 h after the last exercise bout.…”
Section: Methodsmentioning
confidence: 99%
“…Repeated exercise has been shown to improve insulin sensitivity (Borghouts & Keizer 2000, Kirwan et al 2009, Malin et al 2013, Goyaram et al 2014, reduce the catecholamine response to exercise (Kjaer & Galbo 1988), increase lipid catabolism (Phillips et al 1996, Henderson & Alderman 2014, improve arterial compliance and endothelial function (Seals et al 2008, Pierce et al 2011 and maintain both bone density and skeletal muscle mass during ageing (Layne & Nelson 1999) and maintain muscle metabolic capacity with ageing (Olesen et al 2014). Recent work has suggested that both skeletal muscle and adipose tissue function as integrated endocrine organs in response to an exercise stimulus (Pedersen 2013).…”
Section: Introductionmentioning
confidence: 99%